Atomically dispersed Fe–N–C catalyst displaying ultra-high stability and recyclability for efficient electroreduction of CO2 to CO. Issue 15 (30th January 2022) - Dong, Bao-Xia; Peng, Meng-Ting; Zheng, Qiu-Hui; Cao, Si-Min; Teng, Yun-Lei; Zhong, Di-Chang; Li, Zong-Wei
Abstract : By employing N-rich porphyrin-based MOFs PCN-224 and PCN-222 as precursors and adopting a mixed-ligand strategy, uniform dispersions of Fe SA catalysts were obtained with excellent CO2 → CO activity, super-stability, and recyclability. Abstract : To avoid the agglomeration of iron NPs and improve the dispersion of Fe SAs, we employed a mixed-ligand strategy to regulate the iron content in PCN-224(Zn x Fe y ) and PCN-222(Zn x Fe y ). Thanks to the sublimation of Zn and the Kirkendall effect, uniform dispersions of Fe SAs with 1.04–1.06 wt% were obtained in the pyrolysis products Zn0.5 Fe0.5 –N–C-224 and Zn0.5 Fe0.5 –N–C-222 with excellent CO2 → CO activity, super-stability, and recyclability.